An Invariant Protein That Colocalizes With VAR2CSA on Plasmodium falciparum-Infected Red Cells Binds to Chondroitin Sulfate A. (29th October 2021) - Keitany, Gladys J; Jenkins, Bethany J; Obiakor, Harold T; Daniel, Shaji; Muehlenbachs, Atis; Semblat, Jean-Philippe; Gamain, Benoit; Doritchamou, Justin Y A; Desai, Sanjay A; MacDonald, Nicholas J; Narum, David L; Morrison, Robert; et al.
Abstract: Background: Plasmodium falciparum -infected red blood cells (iRBCs) bind and sequester in deep vascular beds, causing malaria-related disease and death. In pregnant women, VAR2CSA binds to chondroitin sulfate A (CSA) and mediates placental sequestration, making it the major placental malaria (PM) vaccine target. Methods: In this study, we characterize an invariant protein associated with PM called P falciparum chondroitin sulfate A ligand (PfCSA-L). Results: Recombinant PfCSA-L binds both placental CSA and VAR2CSA with nanomolar affinity, and it is coexpressed on the iRBC surface with VAR2CSA. Unlike VAR2CSA, which is anchored by a transmembrane domain, PfCSA-L is peripherally associated with the outer surface of knobs through high-affinity protein-protein interactions with VAR2CSA. This suggests that iRBC sequestration involves complexes of invariant and variant surface proteins, allowing parasites to maintain both diversity and function at the iRBC surface. Conclusions: The PfCSA-L is a promising target for intervention because it is well conserved, exposed on infected cells, and expressed and localized with VAR2CSA. Abstract : PfCSA-L, an invariant protein that binds both CSA and VAR2CSA with high affinity, is exported to the iRBC surface and colocalizes with VAR2CSA. PfCSA-L is the target of antibodies in multigravid women and a promising placental malaria vaccine target.